The relationship between parenting Style and the independence of Children Aged 5-6 Years in Nagari Pasia Pelangai - Santika, Elmi; Aini, Wirdatul (Universitas Negeri Padang, 2023)
The background of this research by the low independence of chidren aged 5 to 6 years found in Nagari Pasia Pelangai allegedly becauce parenting style. This study aims to reveal the describtion of parenting style, The independence of children aged 5 to 6 and to reveal relationship between parenting style and the independence of children aged 5 to 6 years in Nagari Pasia Pelangai. This research is a type correlational quantitative research. The population in this study was 60 father and mother. The sampling technique used purposive random. The samples was taken as much as 75% of the population namely 45 people. Data collection techniques using a questionnaire. The data analysis technique uses the percentage formula and product moment correlation formula. The result of this study show: 1) the parenting style practiced by parents is classified as not good; 2) the independence of children aged 5 to 6 years in Nagari Pasia Pelangai is low; 3) there is a signicant relationship between parenting style and the independence of children aged 5 to 6 years in Nagari Pasia Pelangai.Keywords: Parenting style, Independence